Analysis of myocardial salvage with cardiac magnetic ressonance and angiography depending on the STEMI revascularization pathway in a PPCI centre. (3rd October 2022) - De Diego Soler, O; Sanabria, A; Morr, I; Alamar, M; Lorenzatti, D; Prat, S; Doltra, A; Millan, I; Sotes, S; Lopez, T; Ortega-Paz, L; Sabate, M; et al.
Abstract: Background: Reperfusion networks have permitted improvements in reperfusion delays in primary percutaneous coronary intervention (PPCI)-treated ST elevation myocardial infarction (STEMI). However, the impact on myocardial salvage (MS) of direct transfer to the catheterization laboratory (cath-lab) to minimize system delay remains unknown. Objective: We sought to quantify the myocardial salvage index (MSI) acutely and to assess adverse remodeling at 6 months in PPCI-treated STEMI according to the mode of patient presentation. Methods: Between 2005 and 2021 we included 493 patients in a single center registry of first PPCI-treated STEMI who were studied with Late gadolinium enhanced (LGE) cardiac magnetic resonance (CMR) in the acute phase. Among them, 414 (84.0%) underwent a second LGE-CMR at 6 months. Subjects were classified depending on the mode of presentation: those diagnosed out-of-hospital and directly transferred to the cath-lab by the Emergency Medical Services (EMS group, 29.82%); subjects with first medical contact in a PCI-capable hospital (PCI-H group, 41.75%); and patients presenting to a non-PCI-capable center and transferred for PCI (non-PCI-H group, 28.43%). We computed the angiographic area at risk by BARI score, and combined it with the LGE-CMR derived infarct size to compute a validated MSI, expressed as percentage of area at risk. The change in ejection fraction (EF) and indexed left ventricle end-diastolic volume (iLVEDV) from baseline to 6 months was also computed. Results: The mean age was 58.9±11.9 years, 84.5% were male and 51.4% had anterior STEMI. Total median ischaemic time was (median (interquartile range)) 126 (105–161) min in the EMS group, 201 (145–321) min in the PCI-H group and 300 (173–592) min in the non-PCI-H group (p<0.01). MSI was 45.28±2.6%, 39.63±2.2% and 35.53±2.7% respectively (p=0.034). In a multiple linear regression model adjusting for relevant covariables, including initial TIMI flow, area at risk, Killip class, age, sex, diabetes, number of vessels and presence of collaterals, a 7.50% (95% CI 0.9 to 14.1%) increase in MSI was observed in the EMS group compared to the PCI-H group, and 11.03% (95% CI 3.9 to 18.2%) compared to the non-PCI-H group (p=0.027 and 0.003 respectively). At 6 months, the mean absolute increase in EF was 5.36±0.6% for the EMS group, 4.03±0.5% for the PCI-H group and 3.52±0.6% for the non-PCI-H group (p<0.05 in the adjusted analysis) and the increase in iLVEDV was 2.37±7.3, 5.51±6.6 and 18.30±7.6 mL/m 2 respectively (p=0.28). Conclusions: Patients with out-of-hospital diagnostis of STEMI by the EMS who were directly transferred to the cath-lab showed shorter total ischaemic times, resulting in increased myocardial salvage and a trend towards improved indexes of left ventricular function at 6 months. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Grant from La Maratό de TV3 and grant from Fundaciό La Caixa